Caracterização físico-química e análise da qualidade sensorial de azeites de oliva extra virgem brasileiros - Costa, Paulo Ricardo (2017)
Olive oil is one of the most consumed vegetable oils in the world. Its use in the human diet occurs for thousands of years. The climatic requirements for the planting of the tree from which the raw material, the olive tree, is extracted, make the Brazilian territory not suitable for olive growing. As a result, most of the thousands of tons of olive oil consumed in Brazil are imported. The portion of non-imported product is mainly produced in the states of Minas Gerais, Rio Grande do Sul and São Paulo. The justification for analyzing Brazilian olive oils is due to the incipience of studies in this field. This work aims to analyze the physical, chemical, oxidative stability and sensorial analysis with extra virgin olive oil produced in Brazil, comparing with a control product produced outside the country with the justification of proving that the Brazilian product has the same characteristics Or higher than that of a product produced in places with a tradition in olive cultivation. In the analyzes of the acidity index, it was verified that the brands met the requirements established in the legislation, which is 0.8% acidity. In the determination of peroxides all the varieties surveyed were in compliance with the law, which limits to 20 mEq / kg. In the analysis of total phenolic compounds content, mean values of 32.72, 88.86, 488.9 and 510.01 mg / 100g were found in the national products, while in the imported sample used as reference the mean value was 286, 30 mg / 100g. Oxidative stability studies in Rancimat verified high levels of stability in two Brazilian brands, those with oxidation rates lower than the imported product and in direct relation to the content of phenolic compounds. In the optimized quantitative descriptive sensory analysis the tasters identified in Brazilian olive oils positive attributes established by the IOC - International Olive Council such as bitter taste, fruity and spicy taste. In the affective sensorial tests carried out, the trend towards close acceptance between the imported product, with a wider knowledge by the consumers, and three of the four Brazilian brands evaluated was detected. The preference of the majority of the tasters was for the oils with smaller intensities of bitterness and spice and more pronounced fruity flavor.